2012
DOI: 10.1021/am201326b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multifunctional Nanostructured Zinc–Iron Mixed Oxide Photocatalyst by a Simple Solution-Combustion Technique

Abstract: A series of nanostructure zinc-iron mixed oxide photocatalysts have been fabricated by solution-combustion method using urea as the fuel, and nitrate salts of both iron and zinc as the metal source. Different characterization tools, such as X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), diffuse reflectance UV-visible spectra (DRUV-vis), electron microscopy, and photoelectrochemical measurement were employed to establish the structural, electronic, and optical properties of the material. Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…In this study, the enhanced photocatalytic activity was mainly derived from the efficient generation, separation and transfer of the photo-induced electron-hole pairs, which strongly depended on the band structure of the composite photocatalyst [18,40]. BiOBr was a p-type semiconductor, whereas Fe3O4 was a n-type semiconductor.…”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 99%
“…In this study, the enhanced photocatalytic activity was mainly derived from the efficient generation, separation and transfer of the photo-induced electron-hole pairs, which strongly depended on the band structure of the composite photocatalyst [18,40]. BiOBr was a p-type semiconductor, whereas Fe3O4 was a n-type semiconductor.…”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 99%
“…From the analysis, the band gap energy of the resultant coupled zinceiron oxide are 3.36 eV (S1), 3.27 eV (S2), 2.11 eV (S3) and 2.07 eV (S4). It was observed that the increase of iron loading in the coupled zinceiron oxide has reduced the band gap energy of the resultant photocatalyst (Pradhan et al, 2011). The result indicated that the presence of iron (III) oxide has significantly reduced the band gap of pristine zinc oxide.…”
Section: Optical Propertiesmentioning
confidence: 98%
“…AOPs can be characterized by the production of OH radicals due to the ability of these radicals to oxidize and mineralize most of the organic molecules by emitting carbon dioxide gas and inorganic ions (Zaw and Emett, 2002;Black and Veatch, 2010;Meshram et al, 2011;Oller et al, 2011;Pradhan et al, 2011;Tong et al, 2012;Maya-Treviño et al, 2014). Currently, a wide range of AOPs such as Fenton process, Fenton like process, ozonation and photocatalytic process have been well developed and applied in wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations